2019
DOI: 10.21608/edj.2015.71243
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the prevalence of early childhood caries and the associated determinants in a group of preschool children: results from a national oral health survey in Egypt

Abstract: Objective: This study provides information on the prevalence of early childhood caries among a sample of Egyptian Preschool children and the potential determinants associated with this condition. Methods: A total of 651 preschool children were randomly selected from 160 gathering points in 26 governorates in Egypt. A face to face interview was conducted with children's primary caregivers and data on socioeconomic status, oral hygiene practices and feeding habits was collected. Information on caries experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In the last 10-years, studies conducted mainly in Northern Egypt reported an early childhood caries prevalence of 69.6% in 2013 [ 87 ] and 75% in 2014 [ 88 ]. A nationally representative study published in 2019 reported high prevalence (69.2%) with a mean dmft (decayed, missing and filled teeth) score of 3.5 among the 3-to 6-year-old children [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the last 10-years, studies conducted mainly in Northern Egypt reported an early childhood caries prevalence of 69.6% in 2013 [ 87 ] and 75% in 2014 [ 88 ]. A nationally representative study published in 2019 reported high prevalence (69.2%) with a mean dmft (decayed, missing and filled teeth) score of 3.5 among the 3-to 6-year-old children [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Egypt has an ECC problem. The latest national oral health survey showed that the prevalence of ECC was 69.2% [17]. Also, a global study reported that ECC prevalence exceeded 50% [18].…”
Section: Introductionmentioning
confidence: 99%
“…ECC affects 48% of preschool children globally, with geographic variations (2). In Egypt, the prevalence of ECC was 67% (3). The development of ECC is related to dietary habits and the composition of consumed food (4).…”
Section: Introductionmentioning
confidence: 99%